PERAN DAYA DUKUNG WILAYAH TERHADAP PENGEMBANGAN USAHA PETERNAKAN SAPI MADURA - Hartono, Budi (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2012)
Research conducted on the island of Madura. The aim of the research was analyzed the area-based development of beef cattle in Madura island. Primary research data was sourced from statistics in the Madura district in figures. Data was analyzed using Location Quotient (LQ) method. Data procesing conducted whith spreadsheet from Excel on Microsoft Windows 7. The results showed that the basis for the development of Madura cattle each regency were Pamekasan (sub-district Larangan, Pasean, Batumamar, Palengan, Proppo, Tlanakan, and Pegantenan), Sumenep (sub-district Gayam, Nonggunong and Batuputih), Bangkalan (subdistrict Kokop, Geger, Galis, Tanah Merah, and Blega) and Bangkalan (sub-district Ketapang, Sokobanah, Kedungdung, Sampang, Banyuates, Robatal, and Omben. Conclusion of the research was the development of Madura cattle concentrated in the base region of Madura cattle.